1998
DOI: 10.1074/jbc.273.22.14030
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Cdx1and Cdx2Homeotic Genes Leads to Reduced Malignancy in Colon Cancer-derived Cells

Abstract: We have previously described an inverse relationship between Cdx1 and Cdx2 mRNA levels and the extent of dysplasia and severity of clinical outcome in colorectal carcinoma, suggesting that altered expression of these genes was associated with colorectal carcinogenesis or tumor progression. To investigate further their involvement in the physiopathology of colorectal cancer, HT29 colon carcinoma cells that show very low Cdx expression were transfected with Cdx1 and/or Cdx2 cDNA to elicit their overexpression. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 21 publications
6
103
1
1
Order By: Relevance
“…The lower chamber contained 300 ml of growth medium. For the inducible cells, the medium eventually contained doxycycline and was supplemented with 100 nM PMA (Sigma) since parental HT29 cells exhibit a poor intrinsic migration capacity (Mallo et al, 1998). After 24 h, cells having migrated through the filter were fixed with methanol, stained with crystal violet (0.005%) and counted under a microscope in five randomly chosen fields.…”
Section: Migration Assay In Boyden Chambersmentioning
confidence: 99%
“…The lower chamber contained 300 ml of growth medium. For the inducible cells, the medium eventually contained doxycycline and was supplemented with 100 nM PMA (Sigma) since parental HT29 cells exhibit a poor intrinsic migration capacity (Mallo et al, 1998). After 24 h, cells having migrated through the filter were fixed with methanol, stained with crystal violet (0.005%) and counted under a microscope in five randomly chosen fields.…”
Section: Migration Assay In Boyden Chambersmentioning
confidence: 99%
“…22 Several previous reports have suggested a tumorsuppressive role for CDX2 in human colorectal and gastric carcinogenesis. 23 CDX2 expression is associated with not only intestinal mucin phenotypes, 14,24 but also an early tumor stage [24][25][26][27][28][29][30] and improved prognosis in patients with gastric cancer. [29][30][31][32] A previous study reported that CDX2 expression is also correlated with an improved prognosis in patients with ampullary adenocarcinomas.…”
mentioning
confidence: 99%
“…We showed that CDX1 and CDX2 play a role in the development of not only intestinal metaplasia but also ESCC. The roles of CDX1 and CDX2 in carcinogenesis of digestive tract epithelium have been conflicting: there are reports indicating that they function as oncogenic or anti-oncogenic molecules (4,29). Our data may reflect oncogenic function of CDX1/ CDX2 in the development of ESCC since the expression of both genes increased in ESCC.…”
Section: Discussionmentioning
confidence: 63%
“…Some studies of CDX1 and CDX2 suggest that they are important in the early differentiation and maintenance of the intestinal epithelium. For example, in vitro experiments using rodent and human cell lines indicate that modification of CDX1 or CDX2 expression alters cell growth or the intestinal differentiation phenotype (3,4). In vivo observation of CDX genes and their products during mouse development or phenotypic analysis of CDX-gene-mutant mice identifies a role of CDX genes in the maintenance of the intestinal phenotype (5,6).…”
Section: Introductionmentioning
confidence: 99%